Decoding histone ubiquitylation - Chen, Jennifer J.; Stermer, Dylan; Tanny, Jason C. (Frontiers in Cell and Developmental Biology, 2022)
Histone ubiquitylation is a critical part of both active and repressed transcriptional states, and lies at the heart of DNA damage repair signaling. The histone residues targeted for ubiquitylation are often highly conserved through evolution, and extensive functional studies of the enzymes that catalyze the ubiquitylation and de-ubiquitylation of histones have revealed key roles linked to cell growth and division, development, and disease in model systems ranging from yeast to human cells. Nonetheless, the downstream consequences of these modifications have only recently begun to be appreciated on a molecular level. Here we review the structure and function of proteins that act as effectors or “readers” of histone ubiquitylation. We highlight lessons learned about how ubiquitin recognition lends specificity and function to intermolecular interactions in the context of transcription and DNA repair, as well as what this might mean for how we think about histone modifications more broadly.